Does Sustainable Banking Disclosure Affect Bank Efficiency? Evidence from Indonesia - Wihelmina Dea Kosasih; ‪Aulia Fuad Rahman; Arum Prastiwi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: In Indonesia, there are regulatory developments that require companies to implement a sustainable manner in business activities. Based on Financial Service Authority Regulation No. 51/2017 regarding sustainable finance, Bank BUKU 3 and 4 are the first parties required to run and publish a sustainability report. Therefore, it is essential to evaluate the performance of a bank implementing sustainable banking. This study aims to examine sustainable banking disclosure on bank efficiency in Indonesia.Design/Methodology/Approach: The researchers used 70 observations of banks listed on the Indonesian stock exchange from 2015 to 2019. The method for testing bank efficiency employed Data Envelopment Analysis (DEA). In the second stage of the analysis, the researchers utilized a panel data regression method.Research findings: First, the results showed that commercial banks BUKU 3, 4 in Indonesia were still inefficient. Second, the article also found that sustainable banking disclosure had a positive effect on bank efficiency.Theoretical contribution/Originality: This study's results constitute empirical evidence related to stakeholder theory and provide empirical evidence regarding the effect of sustainable banking on bank efficiency.Practitioner/Policy implication: This research contributes to bank management to implement sustainable banking because it can increase bank efficiency.